A simple spectrophotometric method for the determination of trace level lead in biological samples in the presence of aqueous micellar solutions. Issue 5 (2006) - Khan Khan, Humaira Humaira; Ahmed Ahmed, M. Jamaluddin M. Jamaluddin; Bhanger Bhanger, M. Iqbal M. Iqbal
Abstract : A very simple, ultra-sensitive and fairly selective new spectrophotometric method has been developed for the rapid determination of lead(II) at ultra-trace level using 1, 5-diphenylthiocarbazone (dithizone) in presence of aqueous micellar solutions. The proposed method enabled the determination of lead down to µg l −1 in human blood and urine in aqueous media without resource of any "clean-up" step. The most remarkable point of this method is that the presence of micellar system avoids the previous steps of solvent extraction and reduces the cost, toxicity while enhancing the sensitivity, selectivity and the molar absorptivity. The complex formation of lead in blood with dithizone was completed within a minute at room temperature and the absorbance remains stable for 24 h. The average molar absorption coefficient and Sandell's sensitivity were found to be 3.99×10 5 l mol −1 cm −1 and 30 ng cm −2 of Pb, respectively. Linear calibration graphs were obtained for 0.06–60 mg l −1 of Pb II ; the stoichiometric composition of the chelate is 1:2 (Pb:dithizone). The interference from over 60 cations, anions and complexing agents has been studied at 1 mg l −1 of Pb II . The method was successfully used in the determination of lead in several biological samples (human blood and urine and bovine liver), solution containing both lead(II) and lead(IV) and complex synthetic mixtures. The results of biological analyses by the spectrophotometric method were in excellent agreement with those obtained by AAS. The results of lead concentration in biological samples were varied with age, sex and place which have been discussed.